A Global Meta-Analysis of Soil Carbon Stock in Agroforestry Coffee Cultivation - Vanessa Matos Gomes; Marcos Santana Miranda Júnior; Silva, Libério J; Teixeira, Marcus Vinícius; Teixeira, Guilherme; Schossler, Karina; Diego Antônio França de Freitas; Dener Márcio da Silva Oliveira (Agronomy (Basel), 2025)
Given the climate crisis, the search for sustainable production with potential to reduce excess of carbon dioxide (CO2) in the atmosphere has been the subject of global agreements. Soils are fundamental carbon storage systems, with a relevant role in CO2 mitigation emissions. Considering coffee as an important commodity for several countries and agroforestry systems (AFSs) as important allies for mitigating greenhouse gases emitted by the agricultural sector, this study aimed to investigate the ability of coffee plantations in AFSs to mitigate greenhouse gas emissions, through soil carbon sequestration. For this purpose, we performed a meta-analysis of 45 AFSs, including simple and diversified ones, from a detailed literature search of scientific research investigating soil organic carbon in AFSs including coffee cultivation. Overall, no effect of AFSs on carbon stock change rates was found, but an increment of soil carbon storage was observed when comparing AFSs with conventional coffee cultivation. Generally, climatic variables and soil texture positively affect soil carbon stock. When comparing diversified and simple AFSs, the first had a positive effect on carbon stock change rates. Agroforestry coffee showed capacity to mitigate climate effects through carbon storage in the soil, especially when the system is diversified. This is a climate-smart strategy and should be implemented in preference to conventional coffee cultivation.